Cerpen Hamasa An-Nujum Karya Najib Mahfudz: Kajian Sosiologi Sastra: "Hamasa An-Nujum" Short Story by Najib Mahfudz: A Sociological Study of Literature - Noviana, Khoiru Syafa'atin (An-Nahdah Al-'Arabiyah, 2024)
The aim of this research is to determine the social phenomena contained in the short story Hamasa An-Nujum by Najib Mahfudz. NM is an Egyptian writer who is so famous in the field of modern Arabic literature that in 1988 he received the Nobel Prize in literature. Hamasa an-Nujum is one of the short stories in his short story collection which was only published after he died. It contains many social aspects which are a representation of his hometown and childhood. This research uses qualitative descriptive analysis with data analysis techniques used in the form of (1) data reduction, (2) data presentation, and (3) data verification. From this research it can be concluded that in the short story Hamasa An-Nujum by NM there are various social aspects, including socio-cultural aspects, educational aspects, economic aspects, moral aspects and religious aspects. Apart from that, in the author's sociology, it can be seen that NM is a contemporary writer in Arabic literature who was the first to explore the themes of existentialism, so that many of his works represent various human social lives. Among the social values ​​in the short story that are in accordance with the author's social values ​​are the economic, religious and social aspects. Tujuan penelitian ini adalah untuk mengetahui fenomena sosial yang terdapat dalam cerpen Hamasa An-Nujum karya Najib Mahfudz. Najib Mahfudz merupakan seorang penulis Mesir yang begitu terkenal di bidang sastra Arab modern sehingga pada tahun 1988 ia menerima Hadiah Nobel bidang Sastra. Hamasa an-Nujum merupakan salah satu cerpen dalam kumpulan cerpennya yang baru terbit setelah beliau meninggal. Banyak mengandung aspek sosial yang merupakan representasi dari kampung halaman dan masa kecilnya. Penelitian ini menggunakan analisis deskriptif kualitatif dengan teknik analisis data yang digunakan berupa (1) reduksi data, (2) penyajian data, dan (3) verifikasi data. Dari penelitian ini dapat disimpulkan bahwa dalam cerpen Hamasa An-Nujum karya Najib Mahfudz terdapat berbagai aspek sosial, antara lain aspek sosial budaya, aspek pendidikan, aspek ekonomi, aspek moral, dan aspek keagamaan. Selain itu, dalam sosiologi pengarang terlihat bahwa Najib Mahfudz merupakan sastrawan Arab kontemporer yang pertama kali mendalami tema-tema eksistensialisme, sehingga karyanya banyak mewakili berbagai kehidupan sosial manusia. Di antara nilai-nilai sosial dalam cerpen yang sesuai dengan nilai sosial pengarang adalah aspek ekonomi, agama, dan sosial.